Dialog Profetik Nabi Musa dan Allah dalam Al-Qur’an Perspektif Teori Relevansi - Aminullah, Azmi Abdul Muiz; Al Farisi, Mohamad Zaka (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to analyze the implicit meaning in the Qur'anic dialogue using the Relevance Theory proposed by Sperber and Wilson, specifically implicature, inference processes, cognitive effects, and processing effort. The research method used is qualitative, with a library research approach. The research data consist of dialogic utterances in Surah Ṭāhā, verses 17–28. The data source in this study is the text of the Qur'an, specifically Surah Ṭāhā verses 17–28. Data collection is carried out through a literature review, identifying, recording, and classifying the dialogic utterances under analysis. Data analysis is carried out using content analysis techniques. The results of the study show that these utterances function as communicative stimuli that direct interlocutors to the most relevant interpretation through context. These utterances produce significant cognitive effects with relatively minimal processing effort.